2020
DOI: 10.1590/1806-9061-2019-1179
|View full text |Cite
|
Sign up to set email alerts
|

Crude Glycerin and Energy Density of Diets for Growing, Pre-Lay and Pre-Peak Backcob Brown Egg-Laying Hens

Abstract: A total of 320 13-weeks-old pullets were weighed and randomly allocated to treatments comprised by four levels of crude glycerin (0, 3, 6 or 9%) and two levels of ME (metabolizable energy, difference of 100 kcal/kg) in the diets growing (14 to 17 weeks of age), pre-lay and pre-peak (low: 2750, 2800 and 2750 kcal/kg and high: 2850, 2900 and 2850 kcal/kg, respectively). During the study, body weight was registered until 30 weeks of age, feed intake, egg weight and egg-production for each repetition and for indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
(52 reference statements)
0
1
0
1
Order By: Relevance
“…In the liver´s intracellular compartment, oxidation of glycerol can occur to produce energy through glycolysis and the Krebs cycle (Santos, L. et al, 2019;Silva et al, 2014). Studies demonstrated that as an energy source, glycerin can be included on feeding, thus decreasing the cost of feed for ruminants (Costa et al, 2020), swines (Martínez-Miró et al, 2021), birds (Avellaneda et al, 2020) and more recently for fish (Bombardelli et al, 2021b;Matos et al, 2016;Theisen et al, 2020). However, most studies focused on the apparent effects, such as the animal's zootechnical performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the liver´s intracellular compartment, oxidation of glycerol can occur to produce energy through glycolysis and the Krebs cycle (Santos, L. et al, 2019;Silva et al, 2014). Studies demonstrated that as an energy source, glycerin can be included on feeding, thus decreasing the cost of feed for ruminants (Costa et al, 2020), swines (Martínez-Miró et al, 2021), birds (Avellaneda et al, 2020) and more recently for fish (Bombardelli et al, 2021b;Matos et al, 2016;Theisen et al, 2020). However, most studies focused on the apparent effects, such as the animal's zootechnical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Al final del segundo ciclo de postura, disminuyen el desempeño productivo y la calidad del huevo (Melo et al 2019). Se ha hecho bastante investigación en muchos países sobre las características del huevo de primer ciclo de postura (Ramírez et al 2016, Avellaneda et al 2020. Sin embargo, respecto al segundo ciclo, no se conoce mucho sobre las características del huevo ni sobre el nivel de proteína de la dieta.…”
Section: Introductionunclassified